A new strategy for synthesizing silver doped mesoporous bioactive glass fibers and their bioactivity, antibacterial activity and drug loading performance. Issue 73 (21st December 2020) - Qin, Xiang; Cao, Rong; Zheng, Jingjing; Shi, Guojun; Ji, Lijun; Zhu, Aiping; Yao, Hang
Abstract : A new strategy for preparing mesoporous metal-doped bioactive glass fibers. Abstract : A new strategy for preparing mesoporous metal-doped bioactive glass fibers (MBGFs) was designed, which included electrospinning and sulfonating mesoporous PS fibers, precipitating metal ions and bioactive glass sol–gel precursor into the mesoporous polystyrene (PS) fibers and calcinations. Silver-doped mesoporous BGFs (Ag-MBGFs) with a uniform diameter of 1–2 μm and a specific surface area of 40.22 m 2 g −1 were prepared as an example and characterized by SEM, XRD, TG, ICP and FTIR. These Ag-MBGFs showed excellent bioactivity, antibacterial properties and drug loading and release performance due to their special mesoporous and fibrous structure. The concentration of Staphylococcus aureus decreased from 1 × 10 8 colony-forming units per mL (CFU mL −1 ) to 2.5 × 10 6 CFU mL −1 in 2 h and then to 2 × 10 2 CFU mL −1 in 12 h when the concentration of the Ag-MBGFs reached 16 mg mL −1 . BGFs of different compositions and functions could be prepared by the same strategy in a mesoporous PS fiber template, which could enrich materials for constructing orthopedic implants.